المنصات الرقمية للتمويل الجماعي كألية لتشجيع الاستثمار في تمويل المؤسسات الناشئة - حنكة بوبكر; سلخ محمد لمين (University Of Eloued جامعة الوادي, 2023)
يعرف التمويل الجماعي في الآونة الأخيرة معدلات نمو معتبرة في دول العالم العربي، وهو ما قد يجعل من منصات الرقمية للتمويل الجماعي في المستقبل القريب فاعلا أساسيا في مجال تمويل المشروعات، ولا سيما المشروعات المبتكرة التي تعاني من صعوبات الحصول على التمويل أثناء مرحلة تأسيسها . وهذا ما قد يجعل من هذا النوع من التمويل بمثابة صناعة مالية متخصصة تنمو باضطراد ضمن صيغ ومبادرات تطوير فرص الاستثمار القائم على شبكة الأنترنات Abstract: Crowdfunding has recently witnessed significant growth rates in the countries of the Arab world, which may make digital crowdfunding platforms in the near future a major player in the field of project financing, especially innovative projects that suffer from difficulties in obtaining financing during their establishment phase. This may make this type of financing a specialized financial industry that is growing steadily within the formats and initiatives for developing Internet-based investment opportunities.
Intervention
Keywords: التمويل الجماعي; الشركات الناشئة; التمويل; منصات; الاستثمار; crowdfunding.; startups; Financing; platforms; investment.